The old school closet - Jiménez Martínez, Rafael (Avances en Supervisión Educativa, 2007)
Autumn 1988 By Rafael Jiménez Martínez. Honorary Director of the Pedagogical Museum of Aragon. The author started enthusiastically the collection of educational material abandoned in old schools once used by previous generations. The response to his request was both willing and efficient. Quite soon his personal project turned into the whole province´s project and was adopted by all its teachers. One sentence expresses the enthusiasm and excitement that the project provoked: On those old blackboards -some of them just plain black rectangles painted on walls- there still remained some dates, an addition, or a model sentence that looked like broken clouds as the chalk lines had faded away, some pin-men... In a parallel way, some other data have been revealed. For instance, text-books truly became one of the main concerns in the educational policies of those years. New regulations were published as early as August and September 1931, about how to choose text-books and what price and quality they should be. Even a government organization, the Public Education Council, was entrusted to select text-books. All the material collected make up the holdings of the Pedagogical Museum of Aragon.